2003
DOI: 10.1159/000069707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vasoactive Intestinal Peptide and Pituitary Adenylate Cyclase-Activating Polypeptide on Pancreatic, Hepatic and Duodenal Mucosal Bicarbonate Secretion in the Pig

Abstract: Background and Method: The potency of pituitary adenylate cyclase-activating polypeptide (PACAP) and the related vasoactive intestinal peptide (VIP) on pancreaticobiliary and duodenal mucosal bicarbonate secretion (DMBS) was studied in anaesthetized pigs. VIP, PACAP27 and PACAP38 were infused at doses of 250, 500, 1,000, 2,000 and 6,000 pmol/kg·h. Results: Infusion of VIP in these concentrations increased the portal plasma concentrations of VIP from 9 to 102, 220, 600, 850 and 3,795 pM, respectively. At doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…CART resided also in VIP containing fibers innervating the Brunner glands and the gut mucosa. Since VIP is a well established gut secretagogue [50], a role for CART in modulation of VIP mediated secretory functions cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…CART resided also in VIP containing fibers innervating the Brunner glands and the gut mucosa. Since VIP is a well established gut secretagogue [50], a role for CART in modulation of VIP mediated secretory functions cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous injection of PACAP triggers amylase (Mungan et al, 1991;Alonso et al, 1994), pancreatic fluid, bicarbonate, and protein secretions (Naruse et al, 1992;Alonso et al, 1994;Zabielski et al, 1994;Rodríguez-López et al, 1995;Onaga et al, 1996;Wheeler et al, 1997;Lee et al, 1998;Glad et al, 2003). PACAP also induces vasodilation and increases pancreatic blood flow, notably in the exocrine part of the gland (Carlsson et al, 1996;Ito et al, 1998).…”
Section: H Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…PACAP stimulates glucose output from perfused rat liver (Yokota et al 1995) and also in vivo (Sekiguchi et al 1994). PACAP infusion elicited a significant increase in hepatic bicarbonate output in the pig, though only at pharmacological doses, suggesting that PACAP does not play a physiological role in this process (Glad et al 2003). It has also been demonstrated that PACAP induces expression of corticosteroid-binding globulin in cultured fetal hepatocytes (El Fahime et al 1996).…”
Section: Introductionmentioning
confidence: 99%